Conference Notification - Cock, I. E. (Pharmacognosy Communications)
Pharmacognosy Communications is pleased to announce its journal sponsorship of the 15th International Congress of the International Society for Ethnopharmacology, to be held at the Biet Zaman Hotel and Resort, Petra, Jordan between 5 and 8 May, 2015. The Congress will include plenary sessions with invited international and local speakers, as well as parallel colloquia and poster sessions related to the following themes: • Arabian ethnopharmacology. • Arab-European intercultural ethnopharmacology. • Pharmacological and clinical studies of medicinal plants and natural products. • Ethnobotanical approach to drug discovery: strengths and limitations. • Neutraceuticals and dietary supplements – traditional to modern. • Biodiversity and ecological aspects of ethnobotanical sources. • Theory and methodology in the study of ethnopharmacology. • Traditional and modern herbal medicinal products in cosmetology. • Traditional and modern herbal medicinal products in the treatment of cancer. • The ethnoveterinary use of plants in animal health and productivity. • Analytical assays and quality assurance of ethnopharmacological sources.